Analysis of a concrete frame and the impact of its own load and external forces on it - Petrović, Miloš Z.; Petković, Katarina I.; Živulović - Petrović, Marina G.; Jovanović, Emina Z. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The effects of prestressing forces on a reinforced concrete frame ware shown in this paper. The observed system is a statically indeterminate system with two wedging points. It is influenced by two forces, one of Nk = 600 kN and one of its own load. The frame height is 6.00 m and the base distance is 20.00 m. Its own load is due to a girder and the pillars. Constructional load due to prestressing can be conceived as an internal load which is replaced by an equivalent load representing an external one.. This check is performed using the force and deformation method as well as the software program “Tower”. The force method removes the wedging and allows the cross-section to rotate. The statically indeterminate value is then the moment of pinch. In the method of deformation, all the static and deformation values are expressed by a certain number of mutually independent deformation values determined by the equilibrium conditions of the system. The number of independent, deformation indeterminate values presents a deformational ambiguity of a carrier. All deformation ally indeterminate values can be classified into two groups: the first group consists of the angles of rotation with sticks rigidly connected at the ends and the second one consists of the components of node movement. This system has been adopted without eccentricity on the pillars in order to observe the behaviour of the system when it is not in typical and optimal conditions for the sake of proving its functionality i.e. dis-functionality. “Tower 7” is a program for static and dynamic structural analyses and for sizing concrete elements. It is a program for an overall impact analysis in plane and space structures. With tools which are automated, integrated, comprehensive and intuitive, this program allows increasing the speed and quality of designing and the verification of the results obtained by standard methods. Version 7 is a highly-professional tool with high performance. Three different calculation methods have given nearly the same results, with minor differences.